WORLD LITERATURE IN REVIEW. (World Literature Today)
The article reviews several books of world literature including "From the Land of the Moon" by Milena Agus, "Frumoasele străine" by Mircea Cărtărescu, and "En attendant la montée des eaux" by Maryse Condé.